2020
DOI: 10.1093/nar/gkaa598
|View full text |Cite
|
Sign up to set email alerts
|

An NMR-based approach reveals the core structure of the functional domain of SINEUP lncRNAs

Abstract: Long non-coding RNAs (lncRNAs) are attracting widespread attention for their emerging regulatory, transcriptional, epigenetic, structural and various other functions. Comprehensive transcriptome analysis has revealed that retrotransposon elements (REs) are transcribed and enriched in lncRNA sequences. However, the functions of lncRNAs and the molecular roles of the embedded REs are largely unknown. The secondary and tertiary structures of lncRNAs and their embedded REs are likely to have essential functional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…We also showed that IGF1-AS interacts with IGF1 mRNA, creating a 182-bp lncRNA/IGF1 mRNA duplex (Figure S4B), and we do not detect differential expression between small and large dogs for either the lncRNA or IGF1 mRNA (Figure S4C). Knowing that antisense overlapping lncRNAs can regulate mRNA translation rate with no effect on mRNA levels, 29,30 it is possible that IGF1-AS could act as a regulatory mechanism associated with IGF-1 production, perhaps by affecting the affinity of a ribosomal binding motif for the C versus T allele.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…We also showed that IGF1-AS interacts with IGF1 mRNA, creating a 182-bp lncRNA/IGF1 mRNA duplex (Figure S4B), and we do not detect differential expression between small and large dogs for either the lncRNA or IGF1 mRNA (Figure S4C). Knowing that antisense overlapping lncRNAs can regulate mRNA translation rate with no effect on mRNA levels, 29,30 it is possible that IGF1-AS could act as a regulatory mechanism associated with IGF-1 production, perhaps by affecting the affinity of a ribosomal binding motif for the C versus T allele.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…We and ll Structure 29, August 5, 2021 11 others have shown the power of combined methods to structurally investigate large RNAs, including entire mRNA UTRs (Kim et al, 2020;Wacker et al, 2020). In particular, SAXS and NMR together provide complementary structural information (Chen et al, 2012;Rambo and Tainer, 2010), recently applied to long non-coding RNAs (lncRNAs) (Ohyama et al, 2020;Zhang et al, 2019). For IMP target RNA arrays, such approaches are promising for both RNA and IMP RNPs.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Amatuximab was produced by ourselves by subcloning the variable region of SS1_scFv into Fc-expressing vectors as described previously [ 91 , 92 ]. Antibody was produced by transfection of the expression vectors into the production enhanced cell line HEK293_ES1 [ 93 ] expressing the long non-coding SINEUP [ 94 ] targeting heavy and light chains signal peptide on mRNAs. Monoclonal antibody was purified from cell supernatant by protein A affinity chromatography.…”
Section: Methodsmentioning
confidence: 99%